SISTEM INFORMASI AKUNTANSI PENGGAJIAN PEGAWAIDI RSAD WIRA BHAKTI KOTA MATARAM - Syah Arya Jaladara, (2022)
The accounting information system helps management to obtain appropriate information such as giving or paying compensation to employees in the form of salaries and wages. Many problems arise related to salary payment activities, often misuse by irresponsible parties which can cause losses for the company. The purpose of this study was to determine whether Wira Bhakti Hospital had implemented a payroll accounting information system in carrying out the payroll process. This final project uses a case study method with interview techniques. The results of this final project indicate that the payroll system at Wira Bhakti Hospital is quite good and in accordance with existing procedures.